ANALISIS PENGARUH KINERJA JEMBATAN TIMBANG TERHADAP KINERJA PERKERASAN DAN UMUR RENCANA JALAN (Studi Kasus Jembatan Timbang Salam, Magelang) - Arief Fath Atiya; Okty Diana Wulan Sari; Djoko Purwanto; Bagus Hario Setiadji (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
On Keprekan Road – Yogyakarta’s Limit is always crossed by heavy vehicles and sometimes overloaded. On that road found “Jembatan Timbang Salam”. Because of still many phenomena the overloaded vehicles so that “Jembatan Timbang Salam” needs to be revisited its performance in dealing with violations of overloaded that will be effected the pavement performance. From the results of evaluation and analysis carried out,